TDP-43 prevents retrotransposon activation in the Drosophila motor system through regulation of Dicer-2 activity - Giulia Romano; Raffaella Klima; Fabian Feiguin (BMC Biology, 2020)
Abstract Background Mutations in the small RNA-binding protein TDP-43 lead to the formation of insoluble cytoplasmic aggregates that have been associated with the onset and progression of amyotrophic lateral sclerosis (ALS), a neurodegenerative disorder affecting homeostasis of the motor system which is also characterized by aberrant expression of retrotransposable elements (RTEs). Although the TDP-43 function was shown to be required in the neurons and glia to maintain the organization of neuromuscular synapses and prevent denervation of the skeletal muscles, the molecular mechanisms involved in physiological dysregulation remain elusive. Here, we address this issue using a null mutation of the TDP-43 Drosophila homolog, TBPH. Results Using genome-wide gene expression profiles, we detected a strong upregulation of RTE expression in TBPH-null Drosophila heads, while the genetic rescue of the TDP-43 function reverted these modifications. Furthermore, we found that TBPH modulates the small interfering RNA (siRNA) silencing machinery responsible for RTE repression. Molecularly, we observed that TBPH regulates the expression levels of Dicer-2 by direct protein-mRNA interactions in vivo. Accordingly, the genetic or pharmacological recovery of Dicer-2 activity was sufficient to repress retrotransposon activation and promote motoneuron axonal wrapping and synaptic growth in TBPH-null Drosophila. Conclusions We identified an upregulation of RTE expression in TBPH-null Drosophila heads and demonstrate that defects in the siRNA pathway lead to RTE upregulation and motoneuron degeneration. Our results describe a novel physiological role of endogenous TDP-43 in the prevention of RTE-induced neurological alterations through the modulation of Dicer-2 activity and the siRNA pathway.